A COMPARATIVE ANALYSIS OF NARRATIVE TEXT USING THE TRANSITIVITY SYSTEM AND ITS PEDAGOGICAL IMPLICATIONS - Nugraha, Eggy Nurginanjar; Gunawan, Wawan (TELL - US JOURNAL, 2023)
Teaching text has been an issue in the EFL context, especially narrative text that is frequently used in the coursebooks. This study compares a model narrative text from a coursebook with a student narrative text utilizing the transitivity system. The example student imitated the model text when writing her narrative. The analysis results show that despite the similarity of both texts that employ material processes at most in their stories, the student’s text involves more mental processes as the author expresses her mental states throughout the story. This might be caused by two possibilities: (1) The author of the model text uses many subtexts (Seger, 2011) and focuses more on the material process to give the readers an opportunity to interpret the participants' mental states in the story, while the author of the student text has not cognitively reached the use of subtext in a story as she is still a young learner and still in the early developmental phase. Or (2) the author of the student text tries to make the story more personal to engage with the reader as closely as possible. However, as the model text fulfills the social function, generic structure, lexico-grammatical, and experiential process, it influences the sample student's ability to compose a representative narrative text in general. Lastly, these results suggest that EFL teachers should examine the sample text before distributing it to students as a model text and conduct the teaching-learning process with the right genre-based approach stages.